Determination of needs of black aged persons in Port Elizabeth: Direction for future interventions - M. M. S. Ntshona (AOSIS, 1995)
Social, economic and health care needs of elderly black persons in Port Elizabeth and areas in its immediate vicinity are investigated. Conclusions are drawn from a sample study of 301 elderly people. The investigation reveals that the majority of pensioners are -women, their educational standard is below standard 10, and they have little vocational or specialized training. A high proportion (86%) of them are breadwinners and therefore they are unwilling to reside in institutions. Recreational facilities are inadequate. Pension payout points are overcrowded and disorganized. Also health care services are inaccessible to most elderly people. In view of these findings, a community-based approach to care for the elderly is recommended. The approach should promote social interaction among elderly through establishment of luncheon clubs and service centres and well-being of all elderly through geriatric clinics as well as home care services for the infirm. This entails an intersectorial collaboration, with the elderly being fully involved and participating. Considering the exponential growth of the elderly population in South Africa, it is imperative that the government and other organizations should take cognizance of studies of this nature when making future decisions as regards the care of this group.